His Color Space Transformation for Detection of "Pisang Mas" Maturity Based on the Skin Color - Jan William Sianturi; Bagas Aji Wicaksono; Anindia Adyutawati Nugraheni; Robertus Bintoro; Agnes Widianingsih Wulandari; Kristophorus Abel Priambodo (SENATIK STT Adisutjipto, 2018)
Banana is one of the favorite foods in Indonesia, one type of banana that is quite popular is Pisang Mas. Sometimes consumers have difficulty expressing the maturity of bananas at this time. Image processing can be one way to overcome this problem. In this study we will process documented banana images using a method used to change HIS space to extract the characteristics of banana skin color. The characteristic that is taken is the center of the image of a banana that is experienced as much as 15x15 pixels. Images of bananas are 20 pictures for ripe bananas and 20 pictures of raw bananas. The level of success in this study resulted in a value of 100%.